Proposed In‐Training Electrocardiogram Interpretation Competencies for Undergraduate and Postgraduate Trainees. Issue 3 (8th November 2017) - Antiperovitch, Pavel; Zareba, Wojciech; Steinberg, Jonathan S.; Bacharova, Ljuba; Tereshchenko, Larisa G.; Farre, Jeronimo; Nikus, Kjell; Ikeda, Takanori; Baranchuk, Adrian; ,
Abstract : Despite its importance in everyday clinical practice, the ability of physicians to interpret electrocardiograms (ECGs) is highly variable. ECG patterns are often misdiagnosed, and electrocardiographic emergencies are frequently missed, leading to adverse patient outcomes. Currently, many medical education programs lack an organized curriculum and competency assessment to ensure trainees master this essential skill. ECG patterns that were previously mentioned in literature were organized into groups from A to D based on their clinical importance and distributed among levels of training. Incremental versions of this organization were circulated among members of the International Society of Electrocardiology and the International Society of Holter and Noninvasive Electrocardiology until complete consensus was reached. We present reasonably attainable ECG interpretation competencies for undergraduate and postgraduate trainees. Previous literature suggests that methods of teaching ECG interpretation are less important and can be selected based on the available resources of each education program and student preference. The evidence clearly favors summative trainee evaluation methods, which would facilitate learning and ensure that appropriate competencies are acquired. Resources should be allocated to ensure that every trainee reaches their training milestones and should ensure that no electrocardiographic emergency (class A condition) is ever missed. We hope that these guidelines will inform medical education programs and encourage them to allocate sufficient resources and develop organized curricula. Assessments must be in place to ensure trainees acquire the level‐appropriate ECG interpretation skills that are required for safe clinical practice.